The Tor Bue-Bue Demonstration And Motor Development Stimulation Health Education On Children In Sigumuru Village Tapanuli Selatan, 2021 - HOTMA SAUHUR HUTAGAOL (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Based on a preliminary study conducted by researchers in the village of Sigumuru, South Tapanuli Regency, they still found that there were children aged 25-59 months who were shorter than their peers, and none of the 5 children knew about growth and development stimulation activities. the background of the introduction of the tor-tor bue-bue traditional dance skills as an alternative to stimulate growth and development in children in Sigumuru Village, West Angkola District. community service was carried out twice at the Sigumuru Village Head Office. Methods of community service are health education, questions and answers and the practice of tor-tor bue-bue simulation. The target is children aged 4-5 years with their mothers totaling 40 people each divided into 5 groups. health education about the stimulation of children's growth and development before and after health education there is an increase in good knowledge of 37.50%. Health education about alternative ways of stimulating children's growth and development through the tor-tor bue-bue dance before and after health education there is an increase in knowledge of 27.50%. The practice of simulating the tor-tor bue-bue dance as an alternative way of stimulating children's growth and development is quite useful for improving children's skills, where there are 47.50% of children who are skilled in demonstrating the tor-tor bue-bue dance compared to other children who still need guidance and even assistance. to do the dance moves. There was an increase in mother's knowledge in parenting patterns to stimulate children's growth and development and skills in performing the tor-tor bue-bue traditional dance.